Solution-Processed Bulk Heterojunction Solar Cells with Silyl End-Capped Sexithiophene - Choi, Jung Hei; El-Khouly, Mohamed E.; Kim, Taehee; Kim, Youn-Su; Yoon, Ung Chan; Fukuzumi, Shunichi; Kim, Kyungkon (HINDAWI LTD, 2013)
We fabricated solution-processed organic photovoltaic cells (OPVs) using substituted two sexithiophenes, a,w-bis(dimethyl-n-octylsilyl)sexithiophene (DSi-6T) and a,w-dihexylsexithiophene (DH-6T), as electron donors, and [6,6]-phenyl-C-61-butyric acid methyl ester (PCBM) as an electron acceptor. Solution-processed OPVs using DH-6T and DSi-6T showed good photovoltaic properties in spite of their poor solubility. The best performance was observed on DSi-6T:PCBM 1:5 (w/w) blend cell with an open circuit voltage (V-oc) of 0.63V, short circuit current density (J(sc)) of 1.34mA/cm(2), fill factor (FF) of 55%, and power conversion efficiency of 0.44% under AM 1.5G illumination. Although DH-6T has higher hole mobility than DSi-6T, the DSi-6T:PCBM blend cell showed higher hole mobility than DH-6T:PCBM cell. Therefore, DSi-6T cell showed higher device performance than DH-6T cell due to its silyl substitutions, which lead to the increase of the solubility. The incorporation of solution-processed TiO2 interfacial layer in the DSi-6T:PCBM devices significantly enhances FF due to the reduced charge recombination near active layer/Al interface.